Strategy Management: Community Participation in the Implementation of Economy Political Regional Development of Binjai City - Rangkuti, Bachtiar Ahmad Fani; Ramadhan, Muhammad; Menatri, Habibina; Tambunan, Alvira Wiabda Sari (International Conference on Sciences Development and Technology, 2022)
The purpose of this journal is to find out the extent of the role of community participation in the implementation of the Economy Political of regional development in the City of Binjai as a form of community responsibility as an embodiment of strategic management through the potential that exists in the City of Binjai. The qualitative research method was chosen by researchers in this study, using a descriptive analysis approach. The research location used is the City of Binjai. The results of this study indicate that the management strategy on community participation in the implementation of the Economy Political of the development of the Binjai City area has not gone well apart from due to budget constraints so that the implementation of development is not optimal, also because the level of community participation in each sector can be said to be low, this is due to the emergence public apathy to participate in every stage of development.